Effects of hypomagnetic field on adult hippocampal neurogenic niche and neurogenesis in mice - Luo, Yukai; Zhan, Aisheng; Fan, Yunchang; Tian, Lanxiang (Frontiers in Physics, 2022)
The elimination of geomagnetic field (GMF), also called hypomagnetic field (HMF), is one of the major environmental hazards faced by deep-space astronauts and the workers in magnetically shielded rooms on Earth. We previously reported that long-term HMF exposure impaired adult hippocampal neurogenesis (AHN) and cognition by reducing endogenous reactive oxygen species (ROS) levels in adult neural stem cells (aNSCs). In addition to the aNSCs themselves, adult neurogenesis is also regulated by the local environment, i.e. the neurogenic niche. Neurogenic niche is mainly composed of astrocyte, microglia, and vascular system. However, whether the HMF exposure affects the neurogenic niche in hippocampus remains unknown. In this study, we investigated the effects of the HMF exposure on the neurogenic niche and adult neurogenesis in hippocampus, as well as the cognitive function in mice. The HMF is simulated by using the newly upgraded double-wrapped coils, different with our previous coils, which are capable of providing a very low-strength static magnetic field and identical electromagnetic field background between the HMF group and the GMF group. Here, we for the first time clearly revealed that 8-week HMF exposure significantly induced microglia activation and increased the number of astrocytes in hippocampal dentate gyrus (DG), suggesting the abnormalities in the neurogenic niche. Meanwhile, 8-week HMF exposure also markedly reduced proliferation and differentiation of aNSCs in the DG, and impaired the cognitive behavior of mice, consistent with our previous findings. In addition, we also found that 8-week HMF exposure significantly induced anxiety-like behaviors of mice. In summary, this study indicates that 8-week HMF exposure induces the neurogenic niche abnormalities, contributing to the AHN impairments, thus leads to the cognitive dysfunction and anxiety-like behaviors in mice.